ORGANIZATIONAL CITIZENSHIP BEHAVIOR DILIHAT DARI PENGARUH IKLIM SEKOLAH, KEADILAN ORGANISASI, DAN KOMITMEN ORGANISASI - Niko Sudibjo (Jurnal Dinamika Pendidikan, 2020)
Employees who work voluntary more than they assigned are positive things that can advance their organization. The willingness of employees to work voluntarily beyond their duties is called organizational citizenship behavior. This study aims to determine the effect of school climate, organizational justice, and organizational commitment to organizational citizenship behavior in XYZ School Jakarta. With 43 respondents, the data obtained through the questionnaire were analyzed using the PLS SEM method. The results of this study showed that school climate, organizational justice and organizational commitment have a positive effect on organizational citizenship behaviour. Keywords: organizational citizenship behavior, organizational commitment, organizational justice, school climate